2008
DOI: 10.1103/physreve.77.061501
|View full text |Cite
|
Sign up to set email alerts
|

Continuum theory of memory effect in crack patterns of drying pastes

Abstract: A possible clarification of memory effect observed in crack patterns of drying pastes Y. Matsuo, J. Phys. Soc. Japan 74, 1362 (2005)] is presented in terms of a macroscopic elastoplastic model of isotropic pastes. We study flows driven by steady gravitational force instead of external oscillation. The model predicts creation of residual tension in favor of cracks perpendicular to the flow direction, thus causing the same type of memory effect as that reported by Nakahara and Matsuo for oscillated CaCO3 pastes. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…They reported that a preferential crack direction can be made in several types of pastes by shaking a layer of paste before drying. [20][21][22] We investigate the growth processes of quasi-two-dimensional cracks induced by uniform desiccation from the open surface in a thin layer of paste. In this system, cracks are caused by stresses increasing gradually owing to the difference in contraction rate between the paste and the bottom of the container, and are created sequentially to form a typical mud-crack pattern with T-shape intersections in the middle stage of the drying process.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that a preferential crack direction can be made in several types of pastes by shaking a layer of paste before drying. [20][21][22] We investigate the growth processes of quasi-two-dimensional cracks induced by uniform desiccation from the open surface in a thin layer of paste. In this system, cracks are caused by stresses increasing gradually owing to the difference in contraction rate between the paste and the bottom of the container, and are created sequentially to form a typical mud-crack pattern with T-shape intersections in the middle stage of the drying process.…”
Section: Introductionmentioning
confidence: 99%
“…Under such conditions, both the water distribution and elastic deformation of the material can be assumed to be in thermal equilibrium or quasiequilibrium. We also assume that the elastic relaxation is much faster than the redistribution of liquid, and we ignore plasticity, although it is believed to be important for many type of pastes [4,7,8,11,12,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Models which take into account plastic deformation of elastic media under external fields can explain the memory effect of vibration. [26][27][28] Here, there is one big question about the other memory effect, namely the ''memory effect of flow'': some pastes remember the direction of vibration and flow, but others remember only the direction of vibration and cannot remember the flow direction. The emergence of the memory effect of flow depends on what kind of colloidal particles we use.…”
Section: Introductionmentioning
confidence: 99%